The Influence of Dendrite Growth Direction on the Oxidation Behavior of Single-Crystal Superalloy DD10 - WANG Zelei, HU Yebing, CAO Tieshan, CHENG Congqian, ZHAO Jie (Cailiao Baohu)
For investigating the evolution process of surface oxide film on nickel based single crystal superalloys perpendicular and parallel to the direction of primary dendrite growth，the oxidation behavior of nickel based single crystal superalloys DD10 at 1 050 ℃was studied by the method of continuous weight increase.The surface and oxide film morphology，element distribution，etc.of the alloy perpendicular and parallel to the primary dendrite growth direction were analyzed by scanning electron microscopy (SEM)，energy dispersive spectroscopy (EDS)，X-ray diffraction (XRD) and electron probe microanalysis (EPMA).Results showed that the growth direction of dendrites had no effect on the oxidation kinetics and oxide film structure of DD10 alloy.The oxidation kinetics of the alloy in both vertical and parallel planes exhibited a staged phenomenon: The first stage followed the cubic weight gain law，while the second stage followed the asymptotic horizontal line law.Furthermore，the oxide film structure was divided into three layers，with the outer layer composed of columnar Nix(Co)1－xO，the middle layer composed of complex spinel，and the inner layer composed of continuous Al2O3.However，the growth direction of dendrite had a significant effect on the rate of oxidation weight gain of the alloy.The oxidation rate constant of the vertical plane of the alloy was k1 ＝5.96×10－3mg2/(cm4·s)，and the oxidation rate constant of the parallel plane was k2 ＝6.24×10－3 mg2/(cm4·s).Meanwhile，the initial growth rate of the oxide film on the parallel surface of the alloy was greater than that on the vertical surface，which mainly resulted from that the presence of more γ - γ'phase interfaces parallel to the growth direction of the dendrites could provide a large number of non-uniform nucleation sites and more short-circuit diffusion paths for the nucleation of oxides，and thereby cause higher oxidation rates in the first stage for parallel growth directions.With the increase of oxidation time，the inner layers of different dendritic directions all formed a continuous dense Al2O3，which effectively hindered the outward diffusion of metal cations，and reduced the difference in oxidation rates.